You are on page 1of 2

# Angle of Minimum Deviation through a Prism—C.E.

Mungan, Spring 2001 Prove the well-known fact that one gets minimum deviation for a symmetric beam geometry.

φ θ1 θ4 θ2 θ3

γ

1

n

It is easy to see from the geometry of this sketch that the apex angle φ is related to the two internal angles of refraction by
(90˚−θ 2 ) + φ + (90˚−θ 3 ) = 180˚ ⇒ φ = θ 2 + θ 3 ,

(1)

and that the angle of deviation γ is given by

γ = (θ1 − θ 2 ) + (θ 4 − θ 3 ) = θ1 + θ 4 − φ .
We get two more equations by applying Snell’s law to the first interface,
sin θ1 = n sin θ 2 ,

(2)

(3)

and to the second interface,
sin θ 4 = n sin θ 3 .

(4)

But minimum deviation arises when
dγ =0 ⇒ dθ1 dθ 4 = −1 dθ1 dθ 3 dθ1 dθ 2 . dθ1

(5)

using Eq. (2). Now differentiate Eq. (4) with respect to θ1 to get
cosθ 4 dθ dθ 4 = n cosθ 3 3 dθ1 dθ1 ⇒ − cosθ 4 = n cosθ 3

(6)

after substituting Eq. (5). Similarly, differentiate Eq. (1) with respect to θ1 to obtain
dθ 3 dθ =− 2 dθ1 dθ1 ⇒ − cosθ 2 cosθ 4 = − n cosθ 2 cosθ 3

(7)

The second equality follows from substituting the first result into Eq. (6) and pre-multiplying by cosθ2. Again, differentiate Eq. (3) with respect to θ1 and pre-multiply by cosθ3 to give
cosθ 3 cosθ1 = n cosθ 3 cosθ 2 dθ 2 . dθ1

(8)

which is not true. (3) and (4) to obtain (1 − sin2 θ3 )(1 − n 2 sin2 θ2 ) = (1 − sin2 θ2 )(1 − n 2 sin2 θ3 ) which simplifies to sin θ 2 = sin θ 3 assuming n ≠ 1. if this were not the case. Note from Eq. (7) and (8) results in cosθ 3 cosθ1 = cosθ 2 cosθ 4 . then we could optically reverse the ray to prove that there must be two distinct angles of minimum deviation. The only solution to this equation which is consistent with Eq. (3) and (4). (13) . (1) is θ2 = θ3 = 1 φ and so θ1 = θ 4 2 (10) using Eqs. (2) that θ1 = γ min + φ 2 (11) and from Eq. It is also worth remarking on one of the many applications of minimum deviation. (11) into (12) gives a means of determining the index of refraction of a prism of known apex angle. (3) it follows that sin θ1 = n sin φ 2 (12) for minimum deviation. Substituting Eq. Hecht points out a much simpler argument for why θ1 must be equal to θ4 at minimum deviation.Addition of Eqs. Namely. (9) Square this equation and substitute Eqs. + φ γ sin min   2  n= φ sin   2 from a measurement of the angle of minimum deviation. This has the desired symmetry.